THU0114 Efficacy and Safety of Spironolactone in the Treatment of Rheumatoid Arthritis and Ankylosing Spondylitis. (10th June 2014) - Syngle, A.; Verma, I.; Krishan, P.
Abstract : Background: Synthetic disease-modifying antirheumatic drugs (DMARDs) though effective have limitations often requiring use of expensive parenteral biologic DMARDs in Rheumatoid Arthritis (RA) and Ankylosing Spondylitis (AS). Hence there is a need for safe, efficacious economical therapies for management of disease and co-morbidities. Given the TNF inhibiting potential of spironolactone (SPIR) 1, we decided to investigate its use as a novel therapy in RA and AS. Objectives: A randomized, placebo-controlled, open label study to evaluate the efficacy and safety of spironolactone in patients with RA and AS. Methods: A total 73 patients of which 44 of RA (22 in SPIR and 22 in placebo arm) and 29 patients with AS (15 in SPIR and 14 in placebo arm) were randomized to oral SPIR (2 mg/kg/day) or placebo for 12 weeks as an adjunct to existing DMARDs. Patients with active disease (DAS-28 ≥3.2 in RA and BASDAI score ≥4 in AS) with stable doses of conventional DMARDs for at least 6 months were investigated. Clinical response was assessed after 12 weeks by the Disease Activity Score in 28 joints (DAS28), simple disease activity index (SDAI) and American College of Rheumatology (ACR) response criteria for RA and the Bath Ankylosing Spondylitis Activity Index (BASDAI) and Ankylosing Spondylitis Disease Activity Score (ASDAS) for AS patients. Quality of life was assessed using HAQ-DI. Results: The spironolactone and placebo groups were well matched in both RA and AS. After treatment with spironolactone, there was significant reduction (p<0.05) in inflammatory markers (CRP and ESR) and disease activity measures in (DAS-28, SDAI in RA and BASDAI and ASDAS in AS) RA and AS patients (Fig.1A). HAQ-DI score was significantly improved in both RA and AS patients (p<0.02 and p<0.001 respectively) as compared to placebo group. At week 12, ACR 20 and ACR 50 responses were achieved by 68% (n=15) and 27% (n=6) of RA patients respectively in the spironolactone treated group (Fig. 1B), while 18% (n=4) of patients in the placebo group achieved ACR 20 response. There were minor side effects which did not mandate stopping of spironolactone. No change in any biochemical profile was noted after spironolactone treatment. Conclusions: This study suggests that spironolactone significantly reduces inflammatory biomarkers and disease severity and improves physical function assessed by HAQ-DI, which is an excellent predictor of work disability, morbidity. The results suggest spironolactone is a safe, effective adjunctive treatment for RA and AS. References: Bendtzen K et al. Clin Exp Immunol. 2003;134:151–158. Acknowledgements: This study has been supported by a Research Fellowship from University Grant Commission, New Delhi (Govt. of India) [No. F.10-15/2007 (SA-I)]. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.5165